Peptide-Rich Yeast Fractions from Brewer’s Spent Yeast: A Scalable Fractionation Approach and Their Functional Application in Bakery Products - María Emilia Brassesco; Ana Paupério; Carlos D. Pereira; João Paulo Ferreira; Manuela Pintado (Foods)
Brewer’s spent yeast (BSY), a significant brewing by-product, poses environmental challenges and opportunities for valorization as a sustainable protein source. This study focuses on transforming BSY into high-value functional ingredients for food applications. A green, sustainable, and scalable process was developed to extract bioactive compounds from BSY at both laboratory and pilot scales, yielding peptide-rich fractions with robust antioxidant properties. These extracts were incorporated into prototype formulations, including protein-enriched crackers, demonstrating their potential as natural, nutritious ingredients. Physicochemical, compositional, and functional characterizations validated their application viability. The antioxidant potential of BSY fractions was confirmed through total phenolic compounds and ABTS and oxygen radical absorbance capacity assays, where the retentate from the 10 kDa ultrafiltration fraction on the pilot scale exhibited superior bioactivity, supporting its selection as the most suitable fraction for food formulations. Additionally, the transition from laboratory to pilot scale revealed slight variations in protein retention and bioactive compound recovery, emphasizing the need for process optimization. These findings highlight BSY’s potential to support circular economy practices by reducing waste while enhancing the nutritional and functional value of food products.